Improvement of Order Purchasing and Medical Supplies Storing: A Case Study of Hospital Storage Area - โตธนะคุณ นฤทัศน์; พิมพ์สกุล สิทธิพร; หามนตรี เชาวลิต (Engineering and Technology Horizons, 2020)
This research presents an improvement of order purchasing and storing system for medical supplies in hospital storage area. At present, inventory management mainly uses experience of procurement officers leading to improper order quantity. Thus, some medical supplies are overstock and shortage. Researchers collect annual demand of medical supplies which are distinguished by annual usage and risk class of medical supplies (ABC/I-II-III). Researchers focus on medical supplies in group A-III, group A-II, and group A-I and determine order purchasing method for hospital storage management. After implementation of the new order purchasing method, which consists of 3 systems, order quantities of medical supplies decrease by 67.15%, 51.02%, and 57.81%, respectively.